Infectious antibodies in systemic lupus erythematosus patients (2009)
Infections can act as environmental triggers that induce or promote systemic lupus erythematosus (SLE) in genetically predisposed individuals. New technologies, developed recently, enable simultaneous assessment of multiple antibodies. Antibodies to specific infectious agents may shed light into the mechanisms of induction of SLE. The aim of this study was to investigate the prevalence of seropositivity and the titers of antibodies to bacterial, viral, and parasitic agents in SLE patients compared with non-autoimmune controls. Sera from 260 individuals (120 SLE patients and 140 controls) were tested by the BioPlex 2200 Multiplexed Immunoassay method (BioRad) for the prevalence and titers of antibodies to eight infectious agents (Epstein—Barr virus: early antigen IgG, nuclear antigen IgG, viral capsid antigen IgG and IgM, heterophile IgM; cytomegalovirus IgG and IgM; Toxoplasma gondii IgG and IgM; rubella IgG and IgM; Treponema pallidum TPr15G, TPr17G, TPr47G; herpes simplex virus type 1 and 2 IgG; hepatitis C virus and hepatitis B core antibodies. Cytomegalovirus IgM and Epstein—Barr virus early antigen IgG (but not other Epstein—Barr virus antigens) were significantly more prevalent in SLE patients than in controls. Conversely, positive titers of hepatitis B core and rubella IgG antibodies were less prevalent in the SLE patients than in controls. Other differences in titer positivity prevalence were not detected between patients and controls. The titers of the cytomegalovirus IgM, Toxoplasma IgG, Epstein—Barr virus early antigen, and viral capsid antigen IgG antibodies were significantly higher in SLE compared with controls. Our data suggest the importance of previous exposure to infectious agents in the induction and the prevention of SLE. Lupus (2009) 18, 1129—1135.